ASESMEN KOMPETENSI MINIMUM DAN SURVEI KARAKTER DI INDONESIA SERTA RELEVANSINYA DENGAN PEMIKIRAN IBNU SINA - Dewi Ratna Sari; Betty Mauli Rosa (POTENSIA: Jurnal Kependidikan Islam, 2021)
Nadiem Makarim as Minister of Education and Culture of Indonesia explained his ideas about #MerdekaBelajar. One of the points is the replacement of the National Standard School Examination (USBN) into a Minimum Competency Assessment and Character Survey. There are three components which are assessed namely literacy, numeracy and character. This concept needs to be explored by linking it with pre-existing education concepts in order to be assessed about their conceptual and praxis. Through qualitative research library research shows the concept of #Merdeka Belajar is very consistent with Ibn Sina's view of education. Ibn Sina in his writings and concepts also emphasizes the importance of reading, mathematics and science and noble morals. The concept of #MerdekaBelajar and Ibn Sina's thinking in harmony and complementary. Although there are differences in the importance of developing physical aspects that have not been discussed in the Minimum Competency Assessment and Character Survey in Indonesia.